New Downstream Signaling Branches of the Mitogen-Activated Protein Kinase Cascades Identified in the Insect Pathogenic and Plant Symbiotic Fungus Metarhizium robertsii - Tang, Dan; Tang, Xingyuan; Fang, Weiguo (Frontiers in Fungal Biology, 2022)
Fungi rely on major signaling pathways such as the MAPK (Mitogen-Activated Protein Kinase) signaling pathways to regulate their responses to fluctuating environmental conditions, which is vital for fungi to persist in the environment. The cosmopolitan Metarhizium fungi have multiple lifestyles and remarkable stress tolerance. Some species, especially M. robertsii, are emerging models for investigating the mechanisms underlying ecological adaptation in fungi. Here we review recently identified new downstream branches of the MAPK cascades in M. robertsii, which controls asexual production (conidiation), insect infection and selection of carbon and nitrogen nutrients. The Myb transcription factor RNS1 appears to be a central regulator that channels information from the Fus3- and Slt2-MAPK cascade to activate insect infection and conidiation, respectively. Another hub regulator is the transcription factor AFTF1 that transduces signals from the Fus3-MAPK and the membrane protein Mr-OPY2 for optimal formation of the infection structures on the host cuticle. Homologs of these newly identified regulators are found in other Metarhizium species and many non-Metarhizium fungi, indicating that these new downstream signaling branches of the MAPK cascades could be widespread.